1998
DOI: 10.1111/j.1600-0536.1998.tb05946.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of occupational skin diseases during vocational training in baker and confectioner apprentices: a follow‐up study

Abstract: Baker and confectioner apprentices have been included in a prospective follow-up study in the region of East Thuringia, to evaluate risk factors for the development of hand dermatitis. Starting in August 1996, the apprentices have been interviewed and examined in a standardized way right at the beginning (n=91) of their vocational training, 6 (n=79) and 12 months (n=63) later. To gain objective data, TEWL score was also assessed at 3 standardized sites on the hands. In their case histories, 3.3% (n=3) of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 7 publications
1
37
0
11
Order By: Relevance
“…For this purpose a questionnaire for bakers had been adapted from an existing questionnaire for nurses and hairdressers [4,12]. The same questionnaire was used in the previously conducted cohort study from which the control group was recruited [5,6]. The interview and examination performed in the study have been previously described in detail [6].…”
Section: Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose a questionnaire for bakers had been adapted from an existing questionnaire for nurses and hairdressers [4,12]. The same questionnaire was used in the previously conducted cohort study from which the control group was recruited [5,6]. The interview and examination performed in the study have been previously described in detail [6].…”
Section: Schedulementioning
confidence: 99%
“…High loads of wet work, exposure to irritants and atopic skin diathesis have been reported to be the main risk factors for the development of OSDs [6,47]. We and others have shown that hand dermatitis seems to start early during apprenticeship [4,5,43,46], therefore preventive measures should be implemented early in vocational training at occupational schools and companies to achieve optimal efficacy [14,26,52].…”
mentioning
confidence: 97%
“…A law against the addition of potassium persulfate to flour was one of the early steps taken to prevent occupational allergic contact dermatitis (Rietschel and Fowler 1995). Bauer et al (1998) examined baker and confectioner apprentices 2-4 weeks after the start of their training period and after 6 and 12 months of training. Prior to the training period, 3.3% reported having hand eczema.…”
Section: Interventionmentioning
confidence: 99%
“…Jego oceny dokonywano m.in. u uczniów zawodu fryzjera (15,16), piekarza i cukiernika (17), pracowników przemysłu metalowego (18)(19)(20), przetwórstwa rybnego (21), małych zakładów gastronomicznych (22), u zatrudnionych w warunkach niskiej wilgotności powietrza (23), pracowników rafinerii metali nieszlachetnych (24) i działu wysyłkowego drukarni gazet (12). Stosunkowo często badane grupy rekrutowały się ze służby zdrowia, a w ich skład wchodziły uczennice lub studentki szkół pielęgniarskich (15,25), pielęgniarki zatrudnione na sali operacyjnej (26), pielęgniarki geriatyczne (27) czy pracownicy ośrodka neonatologicznego (28).…”
unclassified
“…Takie zjawisko obserwowane było np. u uczniów zawodu piekarza i cukiernika (17), u eksponowanych na chłodziwa podczas obróbki metali (20,21), a także u pracowników rafinerii metali, noszących okluzyjne rękawice (24). Podobne obserwacje dotyczyły pielęgniarek i innych pracowników służby zdrowia.…”
unclassified